Amalan tonggak 12 dan prestasi kerja kakitangan awam : Satu kajian di Universiti Utara Malaysia - Siti Ernie Haziera, Elias (2011)
This study aims to investigate the practices of the 12 Pillars of the performance of support staff working in three academic colleges at the University Utara Malaysia (UUM). Three academic colleges are College of Law, Government and International Studies (COLGIS), College of Business (COB) and the College of Arts and Science (CAS). Issues relating to the performance of public services often receive attention from all walks of life. Failure to obtain satisfactory service has a bad image and bad for the public sector and government in particular, This also creates a negative impression among the people of the ability of the services provided by the government. Therefore, this study is intended to create surveys to gather information with respect to the appreciation of the support staff at the college academic and ethical values against the practice of Pillars 12 and see how far it has affected the performance of the employee concerned. The study was conducted by using questionnaires given to respondents to obtain information. About 150 employees were selected randomly to answer the questionnaire. However, only 93 people who provide feedback via a questionnaire for this study. Data were analyzed using descriptive and inferential analysis. Results showed that women employees are more responsible for their work than male employees. Meanwhile, the four pillars of the 12 elements studied do not have a visible relationship with job performance. Based on the age and academic colleges, the staff has seen more ethical age of their work than employees who are still young. While the staff of COLGIS seen more committed to their work than the staff of the COB and the CAS as well as to improve their work performance